2020
DOI: 10.1007/s40145-019-0357-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of annealing and firing in wet hydrogen on the dielectric breakdown strengths of alumina ceramics

Abstract: Annealing and firing in wet hydrogen are widely used steps in the processing alumina-ceramic insulators that may affect their dielectric breakdown strengths (DBS). In this study, the effects of annealing (at 1300 ℃ for 7 h) and firing in wet hydrogen on the DBS of alumina ceramics (all sintered at 1650 ℃) were studied, and the underlying mechanisms were analyzed by material characterizations. Annealing reduced the DBS of the 95% alumina ceramics due to the inter-granular phase crystallization, and the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Figure shows the structure and performance of the CCTO-NWs@AO and CCTO-NWs@AO/HIPS composites. From the FTIR infrared absorption spectra shown in Figure a, obvious absorption peaks at 1401 and 889 cm –1 are attributed to the longitudinal phonon vibration of Al 2 O 3 and stretching vibration of Al–O. , The emergence of an absorption band near 1640 cm –1 is caused by the deformation vibration of H–O–H of H 2 O on Al 2 O 3 . In addition, no obvious peak in the range of 2400–3400 cm –1 corresponding to O–H further indicates the complete oxidation of Al­(OH) 3 to Al 2 O 3 after high-temperature calcination, with no Al­(OH) 3 residue on the Al 2 O 3 shell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the structure and performance of the CCTO-NWs@AO and CCTO-NWs@AO/HIPS composites. From the FTIR infrared absorption spectra shown in Figure a, obvious absorption peaks at 1401 and 889 cm –1 are attributed to the longitudinal phonon vibration of Al 2 O 3 and stretching vibration of Al–O. , The emergence of an absorption band near 1640 cm –1 is caused by the deformation vibration of H–O–H of H 2 O on Al 2 O 3 . In addition, no obvious peak in the range of 2400–3400 cm –1 corresponding to O–H further indicates the complete oxidation of Al­(OH) 3 to Al 2 O 3 after high-temperature calcination, with no Al­(OH) 3 residue on the Al 2 O 3 shell.…”
Section: Resultsmentioning
confidence: 99%
“…From the FTIR infrared absorption spectra shown in Figure 5a, obvious absorption peaks at 1401 and 889 cm −1 are attributed to the longitudinal phonon vibration of Al 2 O 3 and stretching vibration of Al− O. 43,44 The emergence of an absorption band near 1640 cm In order to further study the nanostructure of CCTO-NWs@AO, high-resolution TEM was carried out, as shown in Figure 5c. The results show that the Al 2 O 3 buffer layer with a thickness of 3 nm is continuously and uniformly grown on CCTO-NW.…”
Section: Thermal Conductivity and Dielectricmentioning
confidence: 99%
“…With the development of current-or electric field-assisted sintering techniques, such as spark plasma sintering (SPS) and micro-wave sintering (MWS), it becomes possible to obtain ceramic materials at a faster speed and lower energy consumption [1][2][3]. Since being first reported by Raj et al [4] in 2010, flash sintering (FS) has been broadly applied to sinter many kinds of ceramics, including YSZ [5][6][7], Al 2 O 3 [8,9], BaTiO 3 [10,11], SiC [12], and ZnO [13,14]. According to these studies, FS makes it possible to sinter highly densified ceramics in a short time at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina ceramics, which exhibit high hardness, high chemical stability, and suitable exure strength, have attracted signi cant attention in recent years, and as a result, they have been commonly used in industry. However, their low fracture toughness limits their further development as a reliable ceramic material, therefore, the toughening and strengthening of Alumina ceramics is a research hotspot of ceramics [10][11][12][13]. The toughening of Al 2 O 3 usually involves two ways: self-toughening and composite material toughening.…”
Section: Introductionmentioning
confidence: 99%